Tackling Public Health Problems with CDATA96 - John Skinner (Elsevier, 1997)
CDATA96. Available from: Australian Bureau of Statistics, St Andrew's House, Sydney Square, Sydney, NSW 2000. Phone (02) 92684634, fax (02) 92684100. $9000 for New South Wales data and a Maplnfo® 4.12 Licence (additional states data costs extra).